2020
DOI: 10.3389/fimmu.2020.575451
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-MOG35-55 Reverses Experimental Autoimmune Encephalomyelitis, Inducing a Peripheral Type 2 Myeloid Response, Reducing CNS Inflammation, and Preserving Axons in Spinal Cord Lesions

Abstract: CNS autoantigens conjugated to oxidized mannan (OM) induce antigen-specific T cell tolerance and protect mice against autoimmune encephalomyelitis (EAE). To investigate whether OM-peptides treat EAE initiated by human MHC class II molecules, we administered OM-conjugated murine myelin oligodendrocyte glycoprotein peptide 35-55 (OM-MOG) to humanized HLA-DR2b transgenic mice (DR2b.Ab°), which are susceptible to MOG-EAE. OM-MOG protected DR2b.Ab° mice against MOG-EAE by both prophylactic and therapeutic applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 58 publications
2
45
2
Order By: Relevance
“…Edil3 has been shown to act as an endogenous homeostasis factor in the central nervous system, protecting neuroinflammation and demyelination through the IL-17/neutrophil inflammatory axis [ 51 ]. Snap25 plays a critical role in synaptic function and is considered an important indicator of neuronal recovery after EAE treatment [ 52 ]. Nrn1 is involved in the survival and differentiation of nerve cells, the growth of axons and dendrites, and the formation and maturation of synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Edil3 has been shown to act as an endogenous homeostasis factor in the central nervous system, protecting neuroinflammation and demyelination through the IL-17/neutrophil inflammatory axis [ 51 ]. Snap25 plays a critical role in synaptic function and is considered an important indicator of neuronal recovery after EAE treatment [ 52 ]. Nrn1 is involved in the survival and differentiation of nerve cells, the growth of axons and dendrites, and the formation and maturation of synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Mannan targets antigens to the mannose receptor, antigens endocytosed for MHC class I or II presentation, and modulation of appropriate T cells [45,[53][54][55][76][77][78][79][80][81]. In relation to autoimmune disorders, mannan conjugates (i) represent a new class of immunoregulators that directly and selectively target a population of immune cells that are implicated in the pathogenesis and progression of disease; (ii) provide first line treatment that selectively tolerates or inactivates disease-inducing cells in patients and also prevents progression of disease by stopping diversification of the autoimmune response to additional epitopes; (iii) allows easier formulation of newly discovered molecules within the mannan matrix platform; and (iv) can achieve block-buster status as a global vaccine drug for efficient treatment of MS [27][28][29][30]. The cyclic-MOG 35-55 peptide, cyclized at the C-and N-terminal amino acids (cyclic-MOG 35-55 ), altered the 3D conformation of the linear MOG 35-55 peptide (Figure 5).…”
Section: Conjugation Of Selective Epitopes With Mannanmentioning
confidence: 99%
“…Results show that mannan-conjugated myelin peptides protect mice against EAE through the expansion of antigen-specific Th1 and Th17 cells with impaired proliferation responses and DC-induced co-stimulatory signals that are required for licensing them to become fully pathogenic T cells [ 28 ]. In another study by Dagkonaki et al [ 29 ], CNS autoantigens conjugated to oxidized mannan were shown to induce antigen-specific T cell tolerance and protection against EAE in mice ( Table 1 ). The results showed that peptides conjugated with mannan induce peripheral type 2 myeloid cell responses and T cell anergy, and suggests that mannan-peptide conjugates may be useful for suppressing antigen-specific CD4+ T-helper cell responses in the context of human autoimmune CNS demyelination [ 29 ].…”
Section: Applied Strategies Utilized Against Msmentioning
confidence: 99%
See 2 more Smart Citations